Drug-selected coexpression of human glucocerebrosidase and P-glycoprotein using a bicistronic vector. - Aran, J M (1994)
Bicistronic cassettes under control of a single promoter have recently been suggested as useful tools for coordinate expression of two different foreign proteins in mammalian cells. Using the long 5' untranslated region of encephalomyocarditis virus as translational enhancer of the second gene, a bicistronic unit composed of cDNA for human P-glycoprotein [the product of the multidrug resistance gene, MDR1 (also called PGY1)] as selectable marker and cDNA for human glucocerebrosidase (GC; EC 3.2.1.45) (a membrane-associated lysosomal hydrolase) was constructed. NIH 3T3 cells transfected with a Harvey murine sarcoma virus retroviral vector carrying this bicistronic cassette (pHaMCG) express active P-glycoprotein and GC and expression of both proteins augments coordinately with selection for increased colchicine resistance. Percoll gradient analysis of homogenates showed that GC was targeted to the lysosomal fraction. The ability to select for expression of GC with natural product drugs after introduction of the pHaMCG retroviral vector may be useful in gene therapy strategies for Gaucher disease.